2014
DOI: 10.1016/j.oooo.2013.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray is a reliable method for immunohistochemical analysis of pleomorphic adenoma

Abstract: Considering the possible loss of cylinders during immunohistochemical reactions, 2.0-mm TMAs in duplicate are a more reliable approach for pleomorphic adenoma immunohistochemical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
(25 reference statements)
1
31
0
1
Order By: Relevance
“…Moreover, analysis of the cytokeratin focused on the biphasic cell differentiation of myoepithelial cell in pleomorphic adenoma has been conducted hence CK7 and CK13 were selected this time 31, 32. In the present study, the small cuboidal cells in solid tumor cell nests showed strong positive reaction to Wnt as well as to β-catenin with nuclear reaction recognized in the latter protein.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, analysis of the cytokeratin focused on the biphasic cell differentiation of myoepithelial cell in pleomorphic adenoma has been conducted hence CK7 and CK13 were selected this time 31, 32. In the present study, the small cuboidal cells in solid tumor cell nests showed strong positive reaction to Wnt as well as to β-catenin with nuclear reaction recognized in the latter protein.…”
Section: Discussionmentioning
confidence: 63%
“…Tissue microarray (TMA) construction was done as previously described (Fonseca et al, 2014). Briefly, tumor areas were selected and marked on hematoxylineosin-stained sections using an objective marker (Nikon Corp, Tokyo, Japan).…”
Section: Tma Constructionmentioning
confidence: 99%
“…Ki-67 is thus the proliferation marker used to assess various types of tumors [16,17]. Expression of Ki-67 may also be used as a proliferation marker and prognostic tool in epithelial salivary gland tumor assessment in adults [18,19]. Faur suggests that Ki-67 expression may be especially useful in assessment of extremely proliferative forms of salivary gland tumors, both benign and malignant [5].…”
Section: Discussionmentioning
confidence: 99%